Cancer Health Economics Research: The Future Is Now. Issue 59 (5th July 2022) - Halpern, Michael T; Lipscomb, Joseph; Yabroff, K Robin
Abstract: The goals of the "Future of Cancer Health Economics Research" virtual conference were to identify challenges, gaps, and unmet needs for conducting cancer health economics research; and develop suggestions and ideas to address these challenges and to support the development of this field. The conference involved multiple presentations and panels featuring several key themes, including data limitations and fragmentation; improving research methods; role and impacts of structural and policy factors; and the transdisciplinary nature of this field. The conference also highlighted emerging areas such as communicating results with nonresearchers; balancing data accessibility and data security; emphasizing the needs of trainees; and including health equity as a focus in cancer health economics research. From this conference, it is clear that cancer health economics research can have substantial impacts on how cancer care is delivered and how related health-care policies are developed and implemented. To support further growth and development, this field should continue to welcome individuals from multiple disciplines and enhance opportunities for training in economics and in analytic methods and perspectives from across the social and clinical sciences. Researchers should continue to engage with diverse stakeholders throughout the cancer community, building collaborations and focusing on the goal of improving health and well-being.